The BIT kit: a protocol for engineer/tech writer communications - Burchard, G. (International Conference on Professional Communication,Communication Across the Sea: North American and European Practices, 1990)
To transform technical information gathered from a large team of programmers into consistent, concise end-user manuals, a small documentation team developed the BIT (bidirectional information transfer) kit, a collection of tools for programmers to use in providing subject matter for software documentation. The BIT kit has helped programmers organize material for use in documentation, helped educate writers about the software, eased communications between programmers and writers, and contributed to consistency in both documentation and program design.< >